Refik Halit Karay’ın eserlerinde II. Meşrutiyet ve “İttihat ve Terakki” - (:unkn) unknown (My University, 2011)
II. Meşrutiyet döneminde yazı hayatına atılan Refik Halit Karay, diğer aydınlar gibi Meşrutiyet’i heyecanla karşılar. Ancak İttihatçılar’ın Meşrutiyet sonrasındaki uygulamaları üzerine hayal kırıklığına uğrar. Tanık olduğu olaylar üzerine İttihat ve Terakki’ye muhalif bir tavır sergiler. Sahip olduğu keskin gözlem gücü ve mizahî bakış açısıyla tenkit-lerini dile getirir. Bu sebeple hayatının beş yıl sürecek olan ilk sürgününü yaşar. Bu yazıda Refik Halit Karay’ın eserlerinde II. Meşrutiyet ve İttihat ve Terakki hakkında yaptığı değerlendirmeler üzerinde durulacaktır.

The Second Constitutional Era and İttihat ve Terakki in the Works of Refik Halit Karay Refik Halit Karay, who begins his writing career during the Second Constitutional period, appreciates this period with excitement like the other intellectuals at the beginning. However later on he becomes dissappointed with the Second Constitutional practices of the Constitu-tional Unionists. He shows objections to the Committee of Union and Progress. Therefore he is forced to live in exile for five years. This study focuses, in his works the evalutations of Refik Halit Karay about the Second Constitutional Monarchy and the Constitutional Unionists.
“İttihat and Terakki” and the second constitution in the novels of Refik Halit Karay
Keywords: Antropoloji